The prevalence of periodontal disease according to oral care habits - Do-hee Kim; Hyun-ju Chung; Ok-su Kim (Oral Biology Research (OBR), 2017)
Periodontal disease is one of the most common chronic diseases. Even though scaling and root planing are helpful for preventing periodontal disease, most people overlook it. So, the purpose of this study was to investigate oral care habits and the prevalence of periodontal disease to improve disease prevention and oral healthcare. This study was based on subpopulation of Donggu, Gwangju, Korea, for people older than 50, where oral examination and panoramic radiography were performed. Oral examination included O`Leary index, BOP (Bleeding on Probing), PD (Probing Depth), and CAL (Clinical Attatchment level). The subjects were 4025 people who responded to a oral health questionnaire. The prevalence of periodontal disease in the subjects were 10.3%, 56.1%, and 33.6% for slight, moderate, and severe periodontitis, respectively. The prevalence of periodontal disease was higher in men and older aged people in general. With respect to oral care habits, when subjects visited a dental center regularly and used oral hygiene devices, the ratio of the O`Leary Index was over 75%, the BOP was less than 25%, and severe PD and CAL (≥7 mm), and the prevalence of periodontal disease was less. Since the prevalence of periodontal disease was higher in male and increased with age, self-motivation about oral care habits, regular dental visits and oral care, such as scaling, root planning, and tooth brushing, are required for these groups. In addition, use of oral hygiene devices, such as dental floss and interdental brushes, is also.